ZmFdC2 Encoding a Ferredoxin Protein With C-Terminus Extension Is Indispensable for Maize Growth - Chen, Yue; Zhong, Deyi; Yang, Xiu; Zhao, Yonghui; Dai, Liping; Zeng, Dali; Wang, Quan; Gao, Lei; Li, Shengben (Frontiers in Plant Science, 2021)
As important electron carriers, ferredoxin (Fd) proteins play important roles in photosynthesis, and the assimilation of CO2, nitrate, sulfate, and other metabolites. In addition to the well-studied Fds, plant genome encodes two Fd-like protein members named FdC1 and FdC2, which have extension regions at the C-terminus of the 2Fe-2S cluster. Mutation or overexpression of FdC genes caused alterations in photosynthetic electron transfer rate in rice and Arabidopsis. Maize genome contains one copy of each FdC gene. However, the functions of these genes have not been reported. In this study, we identified the ZmFdC2 gene by forward genetics approach. Mutation of this gene causes impaired photosynthetic electron transport and collapsed chloroplasts. The mutant plant is seedling-lethal, indicating the indispensable function of ZmFdC2 gene in maize development. The ZmFdC2 gene is specifically expressed in photosynthetic tissues and induced by light treatment, and the encoded protein is localized on chloroplast, implying its specialized function in photosynthesis. Furthermore, ZmFdC2 expression was detected in both mesophyll cells and bundle sheath cells, the two cell types specialized for C4 and C3 photosynthesis pathways in maize. Epigenomic analyses showed that ZmFdC2 locus was enriched for active histone modifications. Our results demonstrate that ZmFdC2 is a key component of the photosynthesis pathway and is crucial for the development of maize.